Can some microbes promote host stress and benefit evolutionarily from this strategy?. (7th December 2020) - Aktipis, Athena; Guevara Beltran, Diego
Abstract: Microbes can influence host physiology and behavior in many ways. Here we review evidence suggesting that some microbes can contribute to host stress (and other microbes can contribute to increased resilience to stress). We explain how certain microbes, which we call "stress microbes, " can potentially benefit evolutionarily from inducing stress in a host, gaining access to host resources that can help fuel rapid microbial replication by increasing glucose levels in the blood, increasing intestinal permeability, and suppressing the immune system. Other microbes, which we term "resilience microbes, " can potentially benefit from making hosts more resilient to stress. We hypothesize that "stress microbes" use a fast life history strategy involving greater host exploitation while "resilience microbes" use a slow life history strategy characterized by more aligned evolutionary interests with the host. In this paper, we review the evidence that microbes affect host stress and explain the evolutionary pressures that could lead microbes to manipulate host stress, discuss the physiological mechanisms that are known to be involved in both stress and microbial activity, and provide some testable predictions that follow from this hypothesis.